Mathematics e-Module with Malay Islamic context for 8th gradestudents: Formative Evaluation on Practicality - Afgani, Muhammad Win; Paradesa, Retni; Khan, Adnan Shahid (Jurnal Pendidikan Matematika RAFA, 2024)
Study aims to determine the practical of Mathematics E-modules on polyhedron using the context of Malay Islam which contains audio visual packaged attractively using the Canva application and makes it easier for students to understand the material. This research uses quantitative descriptive research methods following the formative evaluation stage in one-to-one, small group and field tests. The subjects of this study were 8th grade students at one of junior high school in Palembang which totaled 31 students. This research resulted in (1) E-modules with "Very Practical" criteria in terms of clarity, attractiveness, thoroughness, effectiveness, attractiveness of implementation, user acceptance and durability. The final value of practicality in this study was obtained through instruments in the form of teacher response questionnaires and student response questionnaires as users in field tests and analyzed with quantitative data analysis techniques. The results of the research obtained through the student response questionnaire, the average value of practicality was 85,71% with a very practical category.